Mothers’ experiences as legal guardian of children's phlebitis during hospitalization in Indonesia: A phenomenological study - Casman Casman; Dian Mahanani; Balbina Antonelda Marled Wawo; Muhammad Iqbal; Desy Rizki Ariani; Anung Ahadi Pradana (Belitung Nursing Journal)
Background: Peripheral intravenous catheter (PIVC) insertion is a common procedure performed by nurses for hospitalized children, but phlebitis—an inflammation of the vein—is a frequent complication. The response of the mother, as the child’s primary caregiver, plays a key role in the healing process when phlebitis occurs.